Continuous infusion of beta-lactams: a blissful option for the intensive care unit - Shorr, Andrew F.; Zilberberg, Marya D. (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Antimicrobial resistance remains a growing threat in the care of critically ill patients. Many pathogens previously susceptible to common antibiotics are now resistant to those agents. This pattern exists for both gram-negative and gram-positive organisms. In intensive care units (ICUs) in the United States more than 60% of all isolates of Staphylococcus aureus are methicillin-resistant (1). In Europe, Asia, and the US, many enterobacteriaceae produce extended-spectrum beta-lactamases (ESBLs) which hydrolyze some anti-infectives and which render them resistant to all but carbapenems. Beyond ESBLs, select pathogens are now resistant to carbapenems as well. The prevalence of these carbapenem-resistant enterobacteriaceae (CREs) has more than tripled in Europe since 2010 (2). The situation is no better for Pseudomonas aeruginosa (P. aeruginosa) or Acinetobacter. For example, more than 50% of Acinetobacter are non-susceptible to carbapenems (3). Similarly, among P. aeruginosa, Micek et al. reported that 30% of such organisms recovered in ventilator-associated pneumonia in a cross section of 12 ICUs globally met criteria for multi-drug resistance (4).